Using Test Data in Clinical Practice : a Handbook for Mental Health Professionals. - MacCluskie, Dr. Kathryn C. C. (SAGE Publications, 2002)
Material presented in many testing textbooks is appropriately broad and comprehensive, but the effect for students new to testing is difficulty in then translating the extensive information into the practical skills of administering, scoring, and interpreting tests to help inform the treatment process. Few resources exist to help students and mental health clinicians with the daunting task of learning how to synthesize test data from numerous instruments into a meaningful treatment plan and strategy for a client. This book was written to address that need. It provides readers with clear a.